Determination of the Lowest Coefficient for a One-Dimensional Parabolic Equation in a Domain with Free Boundary - Snitko, H. A. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We establish conditions for the unique solvability of the inverse problem of finding the lower coefficient with two unknown time-dependent parameters in a one-dimensional parabolic equation with integral overdetermination conditions in a domain with free boundary.